Penerapan Hukum Terhadap Tindak Pidana Penyebaran Konten Pornografi Berdasarkan Presfektif Restorative Justice - Fitrah Azizah Alif Permatasari; Deassy Jacomina Anthoneta Hehanussa; Yonna Beatrix Salamor (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: The spread of pornographic content can be qualified as a crime because it fulfills the criminal element, namely the objective element and the subjective element.Purposes of the Research: To analyze and discuss Restorative Justice can be used in solving pornographic cases. Methods of the Research: Normative research, with a statutory approach and a conceptual approach, the problem approach used is literature study. The sources of legal materials used are primary legal materials, secondary legal materials, and tertiary legal materials. Data collection techniques through qualitative analysis methods.Results of the Research: The spread of pornographic content can be qualified as a crime because it fulfills the criminal element, namely the objective element and the subjective element. Law enforcement The application of Restorative Justice can be used in every stage of the criminal justice system and the restorative justice process is only used if the general and specific requirements are met.